2007
DOI: 10.1016/j.neuroimage.2006.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing infants' cortical response to speech using near-infrared spectroscopy

Abstract: Sensitivity to spoken language is an integral part of infants' formative development, yet relatively little is known about the neural mechanisms that underlie the emerging ability to perceive and process speech. This is in large part because there are a limited number of non-invasive techniques available to measure brain functioning in human infants. Near-infrared spectroscopy (NIRS), an optical imaging technique that estimates changes in neuronal activity by measuring changes in total hemoglobin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
119
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 48 publications
11
119
2
Order By: Relevance
“…However, the hemodynamic response in infants does not always present the same characteristics of adults. Some research has found increase in both [oxyHb] and [deoxyHb] (Bortfeld, Wruck, & Boas, 2007;Sakatani, Chenb, Lichtyc, & Zuoa, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…However, the hemodynamic response in infants does not always present the same characteristics of adults. Some research has found increase in both [oxyHb] and [deoxyHb] (Bortfeld, Wruck, & Boas, 2007;Sakatani, Chenb, Lichtyc, & Zuoa, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…This fNIRS system contains three wavelengths (780nm, 805nm, and 830nm) [1,30]. The concentration changes of oxygenated hemoglobin (HBO), deoxygenated hemoglobin (HB) and total hemoglobin (HbT) were measured.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration changes of oxygenated hemoglobin (HBO), deoxygenated hemoglobin (HB) and total hemoglobin (HbT) were measured. The parameters were determined with the modified Beer-Lambert law [1,30]. The international 10-10 system [31] was used to localize the whole prefrontal cortex (PFC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These monitors are used clinically in Japan in rehabilitation/orthopedic settings, in neonatal intensive care units (continuous brain blood flow measured over the fontanelle), and emergency medicine applications. They are approved for research in the U.S. and are used, for example, to assess sensory and motor performance (Bortfeld et al 2007;Hatakenaka et al 2007;Otsuka et al 2007). Sampling occurred every 10sec over a 5 min baseline period, then every 10sec during the 10 min PVT test and during recording of each P50 potential ISI.…”
Section: Near Infrared Spectroscopy (Nirs)mentioning
confidence: 99%